2020
DOI: 10.1080/10408398.2020.1746629
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and risks of beetroot juice consumption: a systematic review

Abstract: Beetroot juice (BRJ) has become increasingly popular amongst athletes aiming to improve sport performances. BRJ contains high concentrations of nitrate, which can be converted into nitric oxide (NO) after consumption. NO has various functions in the human body, including a vasodilatory effect, which reduces blood pressure and increases oxygen-and nutrient delivery to various organs. These effects indicate that BRJ may have relevant applications in prevention and treatment of cardiovascular disease. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 168 publications
(244 reference statements)
0
32
0
1
Order By: Relevance
“…The aforementioned effects attributed to beetroot juice have contributed to an increase in its popularity, and therefore, in its consumption. It has been reported that the global market of beetroot juice increases by 5% every year, a trend that is estimated to remain steady in the following years [9]. In this scenario, the aim of this review article is to analyze the current knowledge regarding the benefits related to the consumption of beetroot and derived food-supplements or formulations, as well as the involved mechanisms of action.…”
Section: Nitratementioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned effects attributed to beetroot juice have contributed to an increase in its popularity, and therefore, in its consumption. It has been reported that the global market of beetroot juice increases by 5% every year, a trend that is estimated to remain steady in the following years [9]. In this scenario, the aim of this review article is to analyze the current knowledge regarding the benefits related to the consumption of beetroot and derived food-supplements or formulations, as well as the involved mechanisms of action.…”
Section: Nitratementioning
confidence: 99%
“…The aforementioned effects attributed to beetroot juice have contributed to an increase in its popularity, and therefore, in its consumption. It has been reported that the global market of beetroot juice increases by 5% every year, a trend that is estimated to remain steady in the following years [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, circulating NO may promote or inhibit tumor growth and metastasis under different conditions depending on its concentration ( Xu et al, 2002 ). Of particular concern is the finding that generation of N-nitroso compounds (NOCs), a potential carcinogen, can be stimulated by acute nitrate ingestion ( Zamani et al, 2020 ). One study has examined effects of beetroot juice on NOC excretion, and results indicate that acute consumption did result in increased levels of NOCs in urine ( Berends et al, 2019 ).…”
Section: Open Questionsmentioning
confidence: 99%
“…There is also no evidence that a diet high in nitrate-rich vegetables increases the risk of cancer – on the contrary, incorporation of vegetables like beetroot and spinach may have protective effects against cancer. While reason for these contrary findings is unknown, high levels of vitamin C in these vegetables could counteract the formation of NOCs and the resulting increase in circulating NO could actually facilitate optimal uptake of tumor-inhibiting phytochemicals ( van Breda & de Kok, 2018 ; Zamani et al, 2020 ). Effects of ingested nitrate seem to be context-dependent, in that it is potentially carcinogenic only on the background of intake with dietary amines or amides as found in red and cured meats ( Koch et al, 2017 ).…”
Section: Open Questionsmentioning
confidence: 99%
“…On the other hand, consumption of high levels of nitrate may be a potential health risk. This is related with the endogenous formation of N-nitroso compounds, which are recognized as carcinogenic, and may also induce several other adverse effects [58]. However, some may consider the nitrates found in beetroot as an important nutrient from the health point of view [26].…”
Section: Potential Use Of Beetroot For the Development Of Functionalmentioning
confidence: 99%